Binder-free graphene as an advanced anode for lithium batteries. Issue 18 (14th January 2016) - Sun, Haiyan; Del Rio Castillo, Antonio Esau; Monaco, Simone; Capasso, Andrea; Ansaldo, Alberto; Prato, Mirko; Dinh, Duc Anh; Pellegrini, Vittorio; Scrosati, Bruno; Manna, Liberato; Bonaccorso, Francesco
Abstract : A binder-free graphene anode for Li-ion batteries showing a reversible specific capacity of ∼500 mA h g −1 after 100 cycles is demonstrated. Abstract : We report the fabrication of binder-free anodes for lithium-ion batteries (LIBs) based on graphene nanoflakes on-demand designed and produced by liquid phase exfoliation of graphite. A solvent exchange process is exploited to first remove the N -methyl-2-pyrrolidone used for the exfoliation of graphite and then to re-disperse the exfoliated single-(SLG) and few-layer (FLG) graphene flakes, at a high concentration (∼5 g L −1 ), in an environmentally friendly solvent, i.e., ethanol. Anodes are realized by drop-casting the SLG- and FLG-based ink in ethanol under ambient conditions on a Cu foil without any binder or conductive agents, typically used for the fabrication of conventional LIBs. We tested our SLG- and FLG-based anodes in a half-cell configuration, achieving a reversible specific capacity of ∼500 mA h g −1 after 100 cycles at a current density of 0.1 A g −1, with coulombic efficiency >99.5%. We also tested the SLG- and FLG-based anode in a full-cell configuration, exploiting commercial LiNi0.5 Mn1.5 O4 as a cathode. The battery operates around 4.7 V with a flat-plateau voltage profile and a reversible specific capacity of ∼100 mA h g −1 . The proposed electrode fabrication process is fast, low cost and industrially scalable opening the way to the optimization of energy and power densities, lifetime and safety of LIBs, while minimizing their cost and environmental impact.